(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article examines the representation of linguocultural elements in Uzbek language educational corpora. It analyzes the connection between language and culture, focusing on how linguocultural elements are explained to students and how they can be applied in language learning. The role of national values, traditions, and historical elements in Uzbek language educational materials is highlighted, showing their significance in enhancing students’ cultural understanding. The study emphasizes the importance of developing communicative competence by understanding linguocultural elements and their effective use in the learning process.